Risk assessment and predation potential of Stratiolaelaps scimitus (Acari: Laelapidae) to control Varroa destructor (Acari: Varroidae) in honey bees. - Sabrina Rondeau (PLoS ONE, 2018)
The biocontrol of the honey bee ectoparasite Varroa destructor is an underexploited but promising avenue that would benefit from being integrated in a Varroa management program. Our study aimed to investigate the potential of the predatory mite Stratiolaelaps scimitus to control Varroa infestations in honey bees. Tests on safety and predation were carried out to: (1) assess the risk of predation of the honey bee brood by S. scimitus under laboratory conditions and within the colony, and (2) evaluate the predation potential of S. scimitus on phoretic Varroa mites. Under laboratory conditions, S. scimitus was able to feed upon free Varroa mites, but also attacked every unprotected honey bee brood stages with a strong preference for bee eggs. When introduced inside colonies, however, S. scimitus does not have negative effects on the survival of the bee brood. Moreover, observations made in the laboratory revealed that S. scimitus does not attack Varroa mites when they are attached to the body of bees. However, all Varroa mites that had naturally fallen from the bees were predated upon by S. scimitus and died in less than 24h. This study provides evidence that S. scimitus does not represent a significant threat to the bee brood, but also suggests that its effect in Varroa control will probably be limited as it does not attack phoretic Varroa mites. Our results represent a first step in assessing the potential of S. scimitus to control V. destructor and provide novel information about the predator's behavior inside the honey bee colony.